2020
DOI: 10.1002/cnr2.1261
|View full text |Cite
|
Sign up to set email alerts
|

The matrix metalloproteinase 7 (MMP7) links Hsp90 chaperone with acquired drug resistance and tumor metastasis

Abstract: Background: Cancer emergence is associated with a series of cellular transformations that include acquired drug resistance followed by tumor metastasis. Matrix metalloproteinases (MMPs) and Hsp90 chaperone are implicated in tumor progression, however, they are not studied in the context of drug resistance. Aims: In the present study, we aimed at understanding the cross-talk between acquired drug resistance and tumor progression, linking MMP7 and Hsp90. Methods and results: We have developed an in vitro model s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 47 publications
(118 reference statements)
1
8
0
Order By: Relevance
“…The effect of silybin on MMPs may also be produced via the TGF-β pathway. 22 These need to be studied in depth in subsequent experiments.…”
Section: ■ Discussionmentioning
confidence: 99%
“…The effect of silybin on MMPs may also be produced via the TGF-β pathway. 22 These need to be studied in depth in subsequent experiments.…”
Section: ■ Discussionmentioning
confidence: 99%
“…High MMP-7 level is an independent predictor of docetaxel resistance and poor cancer survival in patients with castration-resistant prostate cancer (CRPC) [ 59 ]. Enhanced drug efflux activity was found to be correlated with induced expression and activity of MMP-7 in a HSP-90 dependent manner [ 60 ]. Activation of MMP-7 by DKK1 and Wnt/β-catenin pathway is known to induce T-DM1 or ado-trastuzumab resistance, and lead to poor prognosis in gastric adenocarcinoma [ 61 ].…”
Section: Discussionmentioning
confidence: 99%
“…Establishing a vincristine-cisplatin resistant human carcinoma cells (KB), A. Sridhar and colleagues showed that a cross talk between matrix metalloprotease 7 (MMP 7) and heat shock protein 90 (HSP90) could facilitate tumor progression and metastatic potential besides leading to acquired drug resistance. 6 They also demonstrated that enhanced homing in MMP7 overexpressing tumor cells could be inhibited using the HSP90 inhibitor 17-allylamino-17-demethoxygeldanamycin (17-AAG). 6 Since MMP7 inhibitors are already undergoing clinical trials, while HSP90 inhibitors are awaiting approval, their findings provide a novel approach for overcoming drug resistance by targeting simultaneously MMP7 and HSP90.…”
mentioning
confidence: 99%
“…Establishing a vincristine–cisplatin resistant human carcinoma cells (KB), A. Sridhar and colleagues showed that a cross talk between matrix metalloprotease 7 (MMP 7) and heat shock protein 90 (HSP90) could facilitate tumor progression and metastatic potential besides leading to acquired drug resistance. 6 They also demonstrated that enhanced homing in MMP7 overexpressing tumor cells could be inhibited using the HSP90 inhibitor 17‐allylamino‐17‐demethoxy‐geldanamycin (17‐AAG). 6 Since MMP7 inhibitors are already undergoing clinical trials, while HSP90 inhibitors are awaiting approval, their findings provide a novel approach for overcoming drug resistance by targeting simultaneously MMP7 and HSP90.…”
mentioning
confidence: 99%
See 1 more Smart Citation